HUKUM PERDATA DI ERA DIGITAL: PERLINDUNGAN DATA PRIBADI DAN KONTRAK ELEKTRONIK DALAM TRANSFORMASI TEKNOLOGI - Gunawan Widjaja (Berajah Journal, 2026)
Indonesian civil law is undergoing a digital transformation through the protection of personal data (Personal Data Protection Act No. 27/2022) and electronic contracts (Electronic Information and Transactions Act & Government Regulation on Electronic Transactions No. 71/2019), which adapt the Civil Code to the era of AI, blockchain and e-commerce—projected to be worth Rp 4,500 trillion by 2026— where personal data is recognised as a non-material asset with subject rights such as the right to be forgotten and penalties of 2% of global turnover, whilst electronic contracts are valid under Article 18 of the ITE Law and TTE, equivalent to authentic evidence for pacta sunt servanda. This normative literature review identifies challenges including 156 million data breach cases, the vulnerability of digital logs as evidence, consumer information asymmetry, and the weakness of cross-border ODR, thereby recommending reforms to the Civil Code for digital assets, an independent Data Protection Authority, a national ODR platform, and the integration of mandatory data protection clauses to ensure progressive civil legal certainty.